Federal Democratic Republic of Ethiopia Diagnostic Review of Financial Consumer Protection - World Bank Group (World Bank, Washington, DC, 2018)
The objective of the Diagnostic Review of Financial Consumer Protection in Ethiopia is to assess the legal, regulatory, and institutional framework for financial consumer protection (FCP) and develop prioritized and tailored recommendations aimed at supporting the National Bank of Ethiopia (NBE) in developing and operationalizing improvements to that framework. The assessment is conducted under the Ethiopia Financial Inclusion Support Framework (FISF) Program, and based on the revised and enhanced 2017 Edition of the World Bank Good Practices for Financial Consumer Protection with focus on retail products and services in four sectors: i) banks and non-bank financial institutions (NBFIs); ii) payments; and iii) insurance. Further, the review covers five topics in each of the above-mentioned sectors: i) legal, regulatory, and supervisory framework; ii) disclosure and sales practices; iii) fair treatment and business conduct; iv) data privacy; and v) dispute resolution mechanisms. The report reflects the existing legal, regulatory, and institutional framework in Ethiopia, with references to planned reforms that were presented to or discussed with the World Bank team. It also features industry practices identified through interviews with financial services providers, financial regulators, and consumer and industry associations.